Mutational profile of KRAS, NRAS, BRAF, PIK3CA, and AKT1 genes in colorectal cancer patients in a tertiary care hospital, Dhaka - Sharmin Chowdhury; Sheikh Joly Ferdous Ara; Shirazum Monira Mili; Tahani Momotaz; Md Maruf Ahmed Molla; Shaheda Anwar; Ahmed Abu Saleh (Advances in Cancer Biology - Metastasis, 2022)
Background: Colorectal carcinoma (CRC) is the third most common cancer in the world and incidences are on the rise in Bangladesh. KRAS, NRAS, BRAF, PIK3CA, and AKTI gene mutations are predictive markers of biological therapies, monoclonal antibodies targeting EGFR. The purpose of this study was to detect KRAS, NRAS, BRAF, PIK3CA, and AKT1 genes mutation in CRC patients by multiplex real-time Polymerase Chain Reaction (PCR) and evaluate the association of the mutations with clinicopathological features. Methodology: This cross-sectional study was carried out in the Department of Microbiology & Immunology, Bangabandhu Sheikh Mujib Medical University (BSMMU) from March 2019 to January 2020. Tissues from surgically resected colorectal tumors were collected from 44 histopathologically confirmed adult colorectal cancer patients, who were admitted in the Department of Colorectal Surgery, BSMMU. Results: Among 44 histopathologically diagnosed colorectal cancer patients, KRAS, BRAF, and PIK3CA gene mutations were identiﬁed in 31.5%, 4.85%, and 4.85% tumors, respectively. In this study, no mutation was detected in NRAS and AKT1 genes. Concurrent mutation in KRAS and PIK3CA genes were found in one patient. Among the 14 KRAS mutant cases, most (92.85%) were in exon 2 (codon 12/13) and only 7.15% of the mutations were in exon 3 (codon 61). No mutation was detected in codon 59, 117, and 146. Among the two PIK3CA mutations, one was present in exon 9 and another was in exon 20. KRAS mutations were significantly associated with well and moderately differentiated tumors than poorly differentiated tumors (p < 0.05). Histopathologically there was no signiﬁcant association of KRAS mutations with age, sex, tumor location, TNM staging, and other parameters. Conclusion: A combined evaluation of genetic biomarkers can classify about one-third of colorectal cancer patients as mutant for any one of these KRAS, BRAF, and PIK3CA genes.